2015
DOI: 10.1117/12.2181119
|View full text |Cite
|
Sign up to set email alerts
|

Flexible SERS-based substrates: challenges and opportunities toward an Army relevant universal sensing platform

Abstract: Generally the fabrication, assembly and evaluation of plasmonic nanostructures for surface enhanced Raman scattering (SERS) substrates has focused on static rigid substrates such as glass and silicon. However, these static substrates severely limit the application of plasmonic nanostructures as (i) they provide no means to alter the state of assembly of the nanostructures once they are formed or anchored on the surface i.e., not reconfigurable; and (ii) preclude applications which demand non-planar, flexible o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 129 publications
(103 reference statements)
0
3
0
Order By: Relevance
“…26−31 The flexible SERS substrates are recognized as a sensing platform in military applications as well. 32 There are some reports on the fabrication of flexible SERS substrates made from paper, plastic, and other polymer scaffolds. 33−35 In particular, Zhang et al 34 reported a SERS substrate fabrication method using a continuous roll-to-roll (R2R) UV NIL similar to this work.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…26−31 The flexible SERS substrates are recognized as a sensing platform in military applications as well. 32 There are some reports on the fabrication of flexible SERS substrates made from paper, plastic, and other polymer scaffolds. 33−35 In particular, Zhang et al 34 reported a SERS substrate fabrication method using a continuous roll-to-roll (R2R) UV NIL similar to this work.…”
Section: Introductionmentioning
confidence: 99%
“…These SERS-active tapes facilitate the detection of chemical analytes on irregular and nonplanar surfaces. Compared to the traditional SERS substrates such as silicon or glass that are rigid and hard, the flexible substrates such as plastics, nanofibers, and papers are highly sought after for on-field Raman measurements and real-time monitoring of chemical and biological analytes. The flexible SERS substrates are recognized as a sensing platform in military applications as well . There are some reports on the fabrication of flexible SERS substrates made from paper, plastic, and other polymer scaffolds. In particular, Zhang et al reported a SERS substrate fabrication method using a continuous roll-to-roll (R2R) UV NIL similar to this work.…”
Section: Introductionmentioning
confidence: 99%
“…However, traditional SERS substrates are rigid and brittle so are not feasible for some specific applications where variable plasmonic nanostructures and conformable sampling are required [30,31]. Conventional rigid substrates are usually used to detect molecular samples in liquids by dip-coating or dry samples on object surfaces by contact sampling [32].…”
Section: Traditional Rigid Sers Substratementioning
confidence: 99%
“…Direct analysis of surface contaminants has caught the attention of the SERS community, especially in the elds such as homeland security [26][27][28][29] and food quality assurance. [30][31][32][33][34][35] The SERS substrates involved include SERS active nanomaterials, [35][36][37][38] or coinage nanomaterials supported on various exible supporting substances, such as paper, 33,[39][40][41][42][43] polymer, 30 PDMS, 29 sandpaper, 34 and even cotton swabs. 28 Since there is no need for sample pretreatment, the main advantage of the direct surface analysis is that it can greatly streamline the onsite screening process and hence shorten the analysis time.…”
Section: Introductionmentioning
confidence: 99%